Methods of Mathematical Modelling Fractional Differential Equations. - Singh, Harendra; Kumar, Devendra; Baleanu, D. (Dumitru) (Milton : CRC Press LLC, 2019)
This book features original research articles on the topic of mathematical modelling and fractional differential equations. The contributions, written by leading researchers in the field, consist of chapters on classical and modern dynamical systems modelled by fractional differential equations in physics, engineering, signal processing, fluid mechanics, and bioengineering, manufacturing, systems engineering, and project management. The book offers theory and practical applications for the solutions of real-life problems and will be of interest to graduate level students, educators, researchers, and scientists interested in mathematical modelling and its diverse applications. Features Presents several recent developments in the theory and applications of fractional calculus Includes chapters on different analytical and numerical methods dedicated to several mathematical equations Develops methods for the mathematical models which are governed by fractional differential equations Provides methods for models in physics, engineering, signal processing, fluid mechanics, and bioengineering Discusses real-world problems, theory, and applications
6.7 ConclusionReferences; 7 A Hybrid Formulation for Fractional Model of Toda Lattice Equations; 7.1 Introduction; 7.2 Basic Idea of HATM with Adomian's Polynomials; 7.3 Application to the Toda Lattice Equations; 7.4 Numerical Result and Discussion; 7.5 Concluding Remarks; Acknowledgements; References; 8 Fractional Model of a Hybrid Nanofluid; 8.1 Introduction; 8.2 Problem's Description; 8.3 Generalization of Local Model; 8.4 Solution of the Problem; 8.4.1 Solutions of the Energy Equation; 8.4.2 Solution of Momentum Equation; 8.5 Results and Discussion; 8.6 Concluding Remarks; Acknowledgment
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Engineering / Industrial; TECHNOLOGY / Manufacturing; MATHEMATICS / Applied; Mathematical models; Fractional differential equations